101 Timely administration of analgesia. Issue Volume 8: Issue (2018)Supplement 1 (1st March 2018) - Hunt, Clive; Turner, Paul; Pharaoh, Amy
Abstract : Background: An expectation-reality gap exists between the length of time on-request analgesia is requested and the time it is administered. In addition to the physical and psychological benefits of prioritising patient comfort, prompt access to analgesia has been shown to reduce length of hospital stay and improve patient overall satisfaction with care. Objectives: To identify the median time taken from when a patient requests prescribed analgesia to when the analgesia is administered. To consider the feasibility of creating a local standard relating to the time taken from when a patient requests analgesia to when it is administered. Method: Patients on two oncology wards requiring PRN analgesia were invited to participate in a prospective audit. Data collection was via a patient held self-evaluation analgesia request diary. In addition to recording time taken to administer analgesia following request, participants also recorded pain scores and overall satisfaction with care. Written consent was obtained from all participating patients. Results: In total 15 patients were consented although not all patients recruited ultimately returned data. Data was evaluated relating to 16 episodes of administrated analgesia. Oramorph was the analgesia most frequently administered although Naproxen, subcutaneous morphine and Oxycodone MR were also used. Time taken from the patient requesting analgesia to the time it was administered ranged from 4 min to 30 min; the median time was 9.75 min. Conclusion: Despite the lower than expected number of participants recruited into this audit, the audit process highlighted the variable complexities and barriers that exist if aiming to create a Hospital Standard relating to the time taken to administer on request analgesia, these include; type of pharmacology, medicines management policies, environmental and organisational factors. This audit concludes that developing a Pain Pledge may be more apposite than creating a Pain Standard.